Comparison of external and internal training loads in elite junior male tennis players during offensive vs. defensive strategy conditions: a pilot study - Tóth, P. J.; Trzaskoma-Bicsérdy, G.; Trzaskoma, L.; Négyesi, J.; Dobos, K.; Havanecz, K.; Sáfár, S.; Ökrös, C. (Sports, 2025)
The aim of our pilot study was to investigate the effects of offensive and defensive strategy conditions on external and internal training load factors in male tennis players. This study included six elite junior male tennis players (chronological age: 15.7 ± 1.0; body height: 180.7 ± 6.5 cm; body mass: 71.0 ± 10.8 kg) who had to play two simulated matches. Among the external training load variables, running activities were measured with a GPS sensor operating at 10 Hz and a 100 Hz tri-axial piezoelectric linear accelerometer integrated into it; furthermore, tennis shot activities were measured with a tennis racket-mounted smart sensor. Internal training load was measured subjectively using the RPE method. The results show that players scored significantly higher on the PlayerLoad (p = 0.031; r = 0.90) and IMA CoD low right (p = 0.031; r = 0.90) running variables and on the forehand spin (p = 0.031; r = 0.90) and backhand spin (p = 0.031; r = 0.90) when using a defensive strategy. There were no significant differences between the two strategy conditions in all other external and internal training load parameters. The defensive strategy has more acceleration in all three planes of motion, suggesting that conditioning training should be placed in the intermittent endurance capacities for players who predominantly use this strategy.